GROWTH, CARCASS TRAITS AND GAS PRODUCTION IN NELLORE SHEEP FED COMPLETE DIETS SUPPLEMENTED WITH THERMOTOLERANT PROBIOTIC YEAST* (Indian Journal of Animal Production and Management, 2013)
A complete diet was formulated and supplemented with three levels of thermotolerant yeast-Saccharomyces cerevisiae (0 g/kg-control (CON); 1 g/kg (TPY1); 2 g/kg (TPY2) and 3 g/ kg (TPY3) to determine the appropriate level for inclusion in sheep diet by in vitro gas production (IVGP) technique. Eighteen Nellore ram lambs (12.33 ± 0.08 kg initial body weight, aged 3 months) were assigned randomly in the 180 days experiment to one of three groups to see the effect on intake, growth, feed conversion and carcass traits. Treatment diets were no yeast (CON; n = 6), with 1 g/kg mesophilic yeast strain-MTCC-1813 (MPY1; n = 6) and with 1 g/kg thermotolerant yeast strain-OBV-9 (TPY1; n = 6). There was significantly (P
Keywords: Carcass traits; Feed conversion; Growth; In vitro gas production; Nellore ram lambs; Thermotolerant yeast